Analisis Persepsi Konsumen terhadap Penggunaan Aplikasi Livin by Mandiri - Febisatria, Andhi; Adwishanty, Putu Ruth (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze consumer perceptions regarding the use of the Livin by Mandiri mobile banking application. The research is grounded in the Technology Acceptance Model (TAM), focusing on two main constructs: perceived usefulness and perceived ease of use. Data were collected using a qualitative content analysis approach, with user comments on the Google Play Store serving as the primary data source. The findings reveal that while many users express positive attitudes toward the functionality and features of the application, a significant portion also reports dissatisfaction with system performance, user interface, and customer service response times. The study contributes theoretically by validating the applicability of TAM in the context of mobile banking, and practically by offering insights for developers to enhance the user experience of Livin by Mandiri. Furthermore, this research introduces a novel methodological approach by utilizing digital user reviews as a primary data source. It is recommended that future studies incorporate broader data sources, including social media comments and surveys, to strengthen the generalizability of the findings.